2015
DOI: 10.1080/19359705.2015.1007417
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Suicide: The Mental Health Crisis of LGBTQ Youth and How You Can Help

Abstract: symposium were the following: to understand the link between anti-LGBTQ bullying and mental illness and to identify ways to help such patients. To identify the academic research being done on anti-LBGTQ bullying, and how this informs tactics to combat this problem. To identify areas of weakness in the approaches being used, ways to improve them, and areas of future research. To identify ways

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The implications of this study concern not only the health of people who identify as a sexual minority but also the well-being of young people who self-identify as heterosexual yet are perceived as LGB, in addition to those who deviate from the traditional roles imposed by society (Ryan & Rivers, 2003). In terms of practical implications, the present study suggests that sport organizations should target their bullying-intervention on all sports-related contexts (Ahuja et al, 2015). Indeed, early intervention in these environments may help prevent young people from being discouraged to participate in sports due to a fear of being bullied.…”
Section: Resultsmentioning
confidence: 87%
“…The implications of this study concern not only the health of people who identify as a sexual minority but also the well-being of young people who self-identify as heterosexual yet are perceived as LGB, in addition to those who deviate from the traditional roles imposed by society (Ryan & Rivers, 2003). In terms of practical implications, the present study suggests that sport organizations should target their bullying-intervention on all sports-related contexts (Ahuja et al, 2015). Indeed, early intervention in these environments may help prevent young people from being discouraged to participate in sports due to a fear of being bullied.…”
Section: Resultsmentioning
confidence: 87%
“…Prevention messaging needs to proactively identify boys as potential victims in addition to girls, as well as comprehensively represent, protect, and support sexual minority youth. While discussions about sexual identity among high school students have become less taboo in recent years (Ahuja et al, 2015; Graybill & Proctor, 2016), this largely depends on the region and political climate. Beyond tolerance of diversity in sexual identities, violence prevention programs must focus on disrupting homophobia and providing comprehensive support services for these vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, simply being LGBTQ is not a risk factor for depression and suicide. Members of this community do, however, experience higher rates of adverse life events and health disparities that are, in fact, risks for poor mental health outcomes 16‐19 . For example, and related to the current study, a 2016 study 15 reported that LGB high school students are over 3 times more likely than their straight peers to be sexually assaulted.…”
mentioning
confidence: 55%